Retrospective comparison of cortical bone trajectory and pedicle screw in lumbar fusion for patients over 80, including sagittal balance: a single-center study - Giwuk Jang; Seungjun Ryu; Sanghoon Lee; Jeong-yoon Park; Dong-ah Shin; Hoyeol Zhang (BMC Geriatrics)
Abstract Background Comparative studies of posterior lumbar interbody fusion with cortical bone trajectory and pedicle screw in older patients, particularly in those aged ≥ 80 years, are rare. This study aimed to retrospectively analyze the clinical and surgical outcomes following posterior lumbar interbody fusion with pedicle screw fixation compared to cortical bone trajectory in patients aged ≥ 80 years with degenerative lumbar spine disease. Methods We included 68 patients aged ≥ 80 years who underwent degenerative lumbar spinal surgery at our spine center between January 2011 and December 2020. Of these 68 patients, 24 and 44 underwent posterior lumbar interbody fusion with cortical bone trajectory and pedicle screw, respectively. Results The Visual Analog Scale for back pain was significantly lower in the cortical bone trajectory group than in the pedicle screw group at 6 months postoperatively (P = 0.049). The Oswestry Disability Index was significantly lower in the cortical bone trajectory group than in the pedicle screw group at 6 months postoperatively (P = 0.05). The estimated blood loss and operation time were significantly lower in the cortical bone trajectory group than in the pedicle screw group (P = 0.017 and P < 0.001, respectively). Postoperative morbidity was also lower in the cortical bone trajectory group (P = 0.049). Conclusions Despite these limitations, our study findings indicate that cortical bone trajectory is not inferior to posterior lumbar interbody fusion with pedicle screw fixation if there is a need for fusion in older patients aged ≥ 80 years.